Novel Cellular Mechanisms for Neuroprotection in Ischemic Preconditioning: A View from Inside Organelles - Sisalli, Maria Josè; Annunziato, Lucio; Scorziello, Antonella (Frontiers in Neurology, 2015)
Ischemic preconditioning represents an important adaptation mechanism of CNS, which results in its increased tolerance to the lethal cerebral ischemia. The molecular mechanisms responsible for the induction and maintenance of ischemic tolerance in the brain are complex and not yet completely clarified. In the last 10 years, great attention has been devoted to unravel the intracellular pathways activated by preconditioning and responsible for the establishing of the tolerant phenotype. Indeed, recent papers have been published supporting the hypothesis that mitochondria might act as master regulators of preconditioning-triggered endogenous neuroprotection due to their ability to control cytosolic calcium homeostasis. More interestingly, the demonstration that functional alterations in the ability of mitochondria and endoplasmic reticulum (ER) managing calcium homeostasis during ischemia, opened a new line of research focused to the role played by mitochondria and ER cross-talk in the pathogenesis of cerebral ischemia in order to identify new molecular mechanisms involved in the ischemic tolerance. In line with these findings and considering that the expression of the three isoforms of the sodium calcium exchanger (NCX), NCX1, NCX2, and NCX3, mainly responsible for the regulation of Ca2+ homeostasis, was reduced during cerebral ischemia, it was investigated whether these proteins might play a role in neuroprotection induced by ischemic tolerance. In this review, evidence supporting the involvement of ER and mitochondria interaction within the preconditioning paradigm will be provided. In particular, the key role played by NCXs in the regulation of Ca2+-homeostasis at the different subcellular compartments will be discussed as new molecular mechanism proposed for the establishing of ischemic tolerant phenotype.